PENINGKATAN KAPASITAS PENDAPATAN UMKM DODOL PENGLATAN TOKO BU MAWAR DI PENGLATAN KABUPATEN BULELENG-BALI - Fretno Wigiyanto Subali Wagiman,; Nyoman Chandrika Nanda,; Gde Agung Satria, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Penglatan village is one of the villages whose culture still exists even in the current westernization situation. Penglatan village is known for its typical dodol called Dodol Penglatan. Dodol Penglatan has a different uniqueness when compared to other dodol because Dodol Penglatan has quite a variety of flavor variants depending on consumer demand. Marketing strategy has an important role for MSMEs (Micro small and Medium Enterprises). The important role of the right marketing strategy will be able to increase the competitiveness of the products produced by MSMEs. In an effort to develop a marketing strategy, complete information is needed regarding the market, consumers and products needed. Production is the activity of producing goods or services. Usually this activity is carried out in order to add value to the use or benefit of an item or service. Production is an activity that transforms all connectivity that produces activities or activities so that the output or input is goods or services, as well as activities that can support human sustainability.